A Study of the Term 'True and Fair View' in the Context of Accountability - Raziah, Mat Zin (1995)
Historically, as companies grows in size, become more complex and involved in society, so to whom and for what their managers are accountable has also been extended. Until the 19th century, managers of companies and part of public bodies were required to produce accountability reports and submit them for audit. This is because the function of financial report has shifted from stewardship function to performance evaluation and decision usefulness function. Therefore, the auditor’s opinion is very important now since the accountability report audited is being used in making investment decision. A discussion over the need for an interpretation of the term used by auditors in expressing their opinion appears in the accounting literature. But, this does not change the inherent and long-standing vagueness and ambiguity of the undefined term, ‘true and fair’ view which has been used since it was introduced in the 1948 U.K. Companies Act. The term has a legal origin in the 18th Century, and it appears to have been translated into a legal definition concerning corporate accountability in the 20th Century. This change does not only apply in the private sector, but also in some parts of public sector bodies. From this historical study, it is apparent that the changes in the requirement of the disclosure and debate in searching the true definition of ‘true and fair’ was developed together with the accountability process in both sectors. The practitioners were also argued to give certain mystique in the opinion of TFV as a means of demonstrating their professionalism.